Implementasi Metode Tilawati dalam Membaca Al-Qur’an di MTs Al-Ianah Klari Karawang - Fithrotul Hamdah; Sutarjo Sutarjo; Lilis Karyawati (ISLAMIKA, 2022)
This study aims to describe and explain the application of the tilawati method in learning the Qur'an at MTs Al-Ianah Klari, Karawang Regency which describes that the method taught to read the Qur'an becomes easier and looks fun with the application of the tilawati method. in the Qur'an. The learning carried out at MTs Al-Ianah Klari Karawang is always based on the pesantren curriculum, so the author uses the title of this research so that it can be applied especially in the world of education. Basically the author uses the method in research using a qualitative descriptive type of research that combines the opinions of experts with actions that occur in the field which are carried out by observing schools and using other supporting data which includes the title above. The findings that can be found in the field are that MTs Al-Ianah Klari Karawang always applies the tilawati method in learning the Qur'an by using two approach techniques, namely classical demonstrations and listening reading techniques both in groups and individually. The tilawati learning method is carried out through 4 classical techniques, namely classical technique 1 (teacher reading students listening), classical technique 2 (teacher reading students imitating), classical technique 3 (teacher and students reading together), and listening reading technique (one of which is reading people. others listen). While the results obtained from research at MTs Al-Ianah Klari Karawang can be obtained that the activities carried out always prioritize aspects of discipline when taking Tilawati lessons on time, sitting discipline following circular tilawati rules like the letter U, discipline reading the Koran with the rhythm of the song tilawati rost, the discipline of following the teacher's reading while pointing at the readings displayed on the tilawati display, and the discipline of listening and listening to other friends' readings in turn.